Health Volunteers and E-Booklet Impact on Knowledge and Treatment Adherence in Hypertension Patient - Anam, Muhtarul; Christina, Juliana; Rudhiati, Fauziah; Retno A, Tri Hapsari; Waluya, Nandang A. (Poltekkes Kemenkes Jakarta III, 2024)
Hypertension is a disease with a global prevalence of 1.3 billion cases in 2019, which is the leading cause of cardiovascular morbidity and mortality. The prevalence of hypertension in Indonesia is 34.1% among the adult population, with a mortality rate of 427,218. The failure of hypertension patient management is mostly due to a lack of awareness of the importance of adherence to hypertension treatment and a lack of knowledge. This study aims to determine the effect of health education by health volunteers using e-booklet on the knowledge and adherence to treatment of hypertensive patients at Batujajar Health Center area. This study used a quasi-experimental design with intervention and control groups. The sample in this study consisted of 32 respondents, who were selected using the purposive sampling technique. The results showed that health education by health volunteers using e-booklet significantly increased the mean knowledge of hypertensive patients, with the mean value of knowledge rising from 75.6 to 86.8 after the intervention. Patients' adherence to treatment also increased, with the mean value rising from 4.4 to 6. The results showed a significant positive effect on both variables, with a p-value of 0.016 for knowledge and 0.001 for treatment adherence, respectively. Based on the findings, health education conducted by health volunteers using e-booklets significantly impacts the knowledge and medication adherence of hypertension patients in the Batujajar Health Center area. It is recommended that health volunteer training be conducted periodically by healthcare professional and that the e-booklet be utilized as an educational tool at the health center and as a credible reference source for the community.